Gallatin : America's Swiss Founding Father - Dungan, Nicholas (Book collections on Project MUSE., 2016)
In this biography, Dungan charts the rise of Albert Gallatin from Congress to the Treasury to the world of diplomacy. Dungan makes the case that Gallatin's crowning achievement was his central role in the delegation that negotiated the Treaty of Ghent, which brought an end to the War of 1812.